Riding Out the Storm: Out-of-Field Teaching Practice in Indonesia - Esti Rahayu; Shuki Osman (Bina Nusantara University, 2019)
As out-of-field teachers existence led to change in teachers, this research aimed to explore their commitment to learning and teaching, and how their schools supported them. Five Indonesian teachers who started teaching as out-of-field teachers and their school leaders were interviewed for this research. The qualitative case study was employed to explore the problem through interviews, classroom observations, and document analysis. The findings reveal that the initial commitment to teaching, learning, and growing is an investment for further actions throughout the teaching practice. The schools provide necessary assistance through the induction and during their in-service in the provided and requested professional learning, being trusted and acknowledged by school leaders, and having resourceful colleagues. From their schools’ support, the out-of-field teachers become more knowledgeable and remain as teachers for an extended time.